Mengkritisi Implementasi Standar Akuntansi Syariah dalam Pengelolaan Wakaf di Era Society 5.0 - Michelle Prajna Pramewari; Dwi Mutiara; Shofie Azizah; Gunawan Aji (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The era of Society 5.0, characterized by the integration of advanced technologies such as artificial intelligence, Internet of Things (IoT), and big data, has brought significant changes in various aspects of life, including Islamic financial management. Waqf management, as an important financial and social instrument in Islam, requires transparency, effectiveness, and compliance with sharia principles. Sharia Accounting Standards (SAS) serve as a framework to regulate sharia accounting practices in waqf management. This study aims to identify barriers to the implementation of SAS in waqf management in the era of Society 5.0 and explore innovative solutions that can help overcome these barriers. Qualitative methods were used, involving in-depth interviews and document analysis. The results show that a deep understanding of sharia principles, the complexity of accounting standards, and technological dynamics are the main challenges. Innovative solutions such as the utilization of blockchain technology, the development of digital platforms, as well as increased education and collaboration between relevant institutions, can improve effectiveness, transparency, and compliance in waqf management.